Parental corporal punishment and adolescent drinking: the protective role of personal growth initiative and gender difference - Tao, Zhiyuan; Wang, Zhenhai; Yin, Mengyun; Yu, Chengfu; Zhang, Wei; Dong, Haijun (Frontiers in Psychology, 2024)
Introduction Parenting and peer victimization (PV) are crucial for adolescent drinking. To further explore the cause of adolescent drinking, the present study investigated the role of PV and personal growth initiative (PGI) in the relationship between parental corporal punishment (PCP) and adolescent drinking. Methods Present study build moderated mediation models to test the hypothesis, and detailed analysis of gender differences was conducted on the models. The data were collected in a cross-sectional questionnaire study with n = 1,007 adolescents (mean age = 13.16 years, 51.84% girls, n = 522). Results Model analysis showed that: (1) PV totally mediated the relationship between PCP and adolescent girls’ drinking behavior; (2) The positive association between PV and drinking was only significant for girls with low PGI. Discussion These findings underscore the importance of the protective effect of a personality trait characterized by spontaneous self-promotion on adolescent girls’ drinking.